Sennacherib's "Palace without Rival". A Programmatic Study of Texts and Images in a Late Assyrian Palace - Russell, John Malcolm
Ph.D. diss.; Supervisor: Irene J. Winter. Order No. DA8603695. Cf. DissAbstr 46/12 (June 1986) 3518-A.